Pendampingan Kedai Kopi Gumarang untuk Berkembang menjadi Harmonis Space dengan Strategi Menerapkan Elemen-elemen di Kanvas Model Bisnisnya - Eli Ratni; Virtuous Setyaka; Muhammad Idris; Edita Elda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
The business potential for brewed coffee by Baristas is very large, especially coffee beans from Indonesian volcanic soil because they have a prime taste. The Gumarang coffee shop started amid the Covid-19 pandemic, this business can grow and survive, but has not yet developed optimally according to its existing potential. Gumarang operated with production equipment that has a small capacity for dispensing coffee, so it has not been able to meet all consumer demands. Gumarang had the opportunity to develop the business under the guidance of the Mandiri and Merdeka Cooperative (KMDM) so that it could apply the elements of the Business Model Canvas (BMC) concept already had. The value proposition element for Gumarang is the existence of an original type of coffee, namely original Minangkabau coffee cultivated by local West Sumatra farmers. Then there is the Gumarang Signature, which is a formula or recipe owned by the Barista. In addition, Gumarang also provides space and organizing services for community events in the city of Padang with friendly service and a traditional minimalist cafe concept, branded as Harmonis Space. The Gumarang coffee shop which was developed into Harmonis Space requires assistance from academics to stay on the path of the business concept. The method used was training, consultation, and evaluation, by the community engagement team and partners. The ultimate goal of a series of activities is to increase partner income as well as community empowerment to strengthen the family economy.